The Conduct Adjustment Term in the urban planning order as a compensatory instrument of public policies - Florian, Luciana Volpon; Goulart, Jefferson Oliveira (ANAP Brazil, 2025)
Objective – Analysis of the Conduct Adjustment Term as a compensatory instrument for public policies in the urban planning order, suggesting the inclusion of a clause that deals with investments in public policies in favor of local urban development.Methodology – The research, of a qualitative and descriptive nature, was based on a systematic review of bibliography in the areas of Urban Law and Urbanism, from which the history of the Public Prosecutor's Office is traced and the TAC is presented as a legally appropriate instrument to obtain the implementation of public policies compatible with the constitutional statement regarding the social function of the city and property.Originality/Relevance – This is a doubly original study: firstly, due to its theme, namely, the effectiveness and incidence of the Terms of Conduct Adjustment regarding the forms of land subdivision and urban expansion patterns; secondly, due to its object, as the gap in urban studies of non-metropolitan and rural realities is known, since there are significant differences in the contemporary terms in which the processes of urban structuring and restructuring are forged.Results – The TAC in the urban planning order demonstrates institutional viability as a compensatory instrument of public policies and, for its greater guarantee and security of compliance, several measures of effectiveness can and should be inserted, as well as speed and procedural economy in comparison to the processing of a legal action.Theoretical/Methodological Contributions – Due to its original nature, the research has identified few and rare similar studies with which it is possible to establish a dialogue in terms of theoretical focus and methodological approach and which, furthermore, articulate different fields of knowledge, especially Urbanism, Urban and Regional Planning, Public Policies and Urban Law.Social and Environmental Contributions – The inclusion of a clause on compensation in public policies in TAC in the urban planning order contributes to integrating economic development with social rights and a sustainable environment, whose paradoxical reality highlights socio-spatial segregation due to urban expansion patterns characterized by informality and precariousness of urban centers, in order to enhance urban resilience.
Keywords: Conduct Adjustment Term; Public Prosecutor's Office; Urban Policy